Yoga Practice Has Minor Influence on Respiratory Function at Rest in Men and Women (Baltic Journal of Sport and Health Sciences, 2013)
Research background and hypothesis. Hatha yoga breathing has the potential of training the respiratory system in such a way that it helps an individual to cope with the respiratory demand (Ray et al., 2011).Research aim was to compare pulmonary function variables between physically inactive subjects and the ones practicing hatha yoga and to evaluate changes after 6 months of yoga practice in the latter group. Research methods. Pulmonary function was measured by means of the gas analyser “Oxycon Mobile” (Germany) before and after 6 months of yoga training in men (n = 11) (age – 30.8 (7.06), BMI – 25.6 (2.6)) and women (n = 11) (age – 28.9 (6.86), BMI – 22.5 (2.3)) practicing yoga and control subjects (n = 22) of similar age. Measurements included forced vital capacity (FVC), forced expiration volume in one second (FEV(1)), forced inspiratory volume in one second FIV1, vital capacity (VC), peak expiratory flow (PEF), forced expiratory flow rate (FEF (25–75)%), forced inspiratory flow at 50% of the vital capacity (FIF50%), maximum voluntary ventilation (MVV), vital capacity (VC MAX), peak inspiratory flow (PIF), etc.Research results. Pulmonary function measures FEF 75/85 (L/s) (p = 0.036), total volume inspired FVC IN (L) (p = 0.014), FIV1 (L) (p = 0.045) were significantly higher in the group practicing yoga than in the control group of women, and VC MAX (%) (p = 0.018), FEV 1 (%) (p = 0.041), FEF 25 (L/s) (p = 0.017), FVC IN (L) (p = 0.002) in men practicing yoga, than in men not practicing yoga. They also demonstrated higher values of MVV (L/min)  (p = 0.068) and FVC (L) (p = 0.050). After 6 months of practicing yoga we found higher FEF 50 (L/s) (p = 0.003), FEF 50% (L/s) (p = 0.003) in women’s group and VCMAX (%) (p = 0.028) in men’s group. We also found a tendency of the increase of VCMAX (L) (p = 0.053), PIF (L/s) (p = 0.051), FVC IN (L) (p = 0.061), FIVI (L)  (p = 0.064) indexes in men and PIF (L/s) (p = 0.072), FVC IN (L) (p =  0.076) in women.Discussion and conclusions. Yoga practice appeared to have minor influence on respiratory function at rest in men and women of middle age. Additional studies examining various yoga practices are warranted to gain a more comprehensive understanding of the effects of yoga techniques on pulmonary functions.Keywords: pulmonary function at rest, yoga training, yoga breathing.